КОЛЛОКАЦИИ И ЗАИМСТВОВАНИЯ: РУССКО-ПОЛЬСКИЙ СОПОСТАВИТЕЛЬНЫЙ АНАЛИЗ - Białek, Ewa (Studia Rossica Posnaniensia, 2008)
The article focuses on new collocations which are created in Russian and Polish on the basis of borrowings, especially Anglicisms. Particular attention is paid to similarities and differences observable in the processes of loan assimilation in these languages. The analysis of translation strategies and the study of relations between the units of translation and their corresponding equivalents adopted by the translator show that the readiness to the implementation of borrowings and the status of the same loan in the SL and the TL can be different. These factors to some extent determine the choice of occasional equivalents such as caiques, hybrids, or descriptions.